INFLUENCE OF YOGA ON THE MEMORY OF PRACTITIONERS - Mironova O.V. ,; Yarchikovskaya L.V. ,; Khismatullin S.A. ,; Sharonova A.V. ,; Kiprushina I.I. , (Theory and Practice of Physical Culture, 2023)
Objective of the study was to study the effect of yoga classes on the characteristics of short-term and long-term memory in female students. Methods and structure of the study. 42 2nd year students of the Russian State Hydrometeorological University took part in the experiment. The girls were asked to memorize the list of spoken words and, if possible, reproduce it before and after physical activity; the number of words remaining in memory was also counted after one week. Thus, it was experimentally proved that the type of motor activity is not a statistically significant factor in the process under study in the field of short-term memory, however, with delayed reproduction, the memory capacity of female students who practice yoga is statistically significantly higher.